Biomass gasification for syngas and biochar co-production: Energy application and economic evaluation. (1st January 2018) - Yao, Zhiyi; You, Siming; Ge, Tianshu; Wang, Chi-Hwa
Highlights: A gasification model was developed to predict the production of syngas and biochar. Economic value of syngas and biochar production was evaluated based on the model. The heat and mass transfer in the reactor was modelled by a three-region approach. The effects of various factors on syngas and biochar production were studied. Abstract: Syngas and biochar are two main products from biomass gasification. To facilitate the optimization of the energy efficiency and economic viability of gasification systems, a comprehensive fixed-bed gasification model has been developed to predict the product rate and quality of both biochar and syngas. A coupled transient representative particle and fix-bed model was developed to describe the entire fixed-bed in the flow direction of primary air. A three-region approach has been incorporated into the model, which divided the reactor into three regions in terms of different fluid velocity profiles, i.e. natural convection region, mixed convection region, and forced convection region, respectively. The model could provide accurate predictions against experimental data with a deviation generally smaller than 10%. The model is applicable for efficient analysis of fixed-bed biomass gasification under variable operating conditions, such as equivalence ratio, moisture content of feedstock, and air inlet location. The optimal equivalence ratio was found to be 0.25 for maximizing the economic benefits of the gasification process.